2016
DOI: 10.1038/ncomms10750
|View full text |Cite
|
Sign up to set email alerts
|

Selective labelling and eradication of antibiotic-tolerant bacterial populations in Pseudomonas aeruginosa biofilms

Abstract: Drug resistance and tolerance greatly diminish the therapeutic potential of antibiotics against pathogens. Antibiotic tolerance by bacterial biofilms often leads to persistent infections, but its mechanisms are unclear. Here we use a proteomics approach, pulsed stable isotope labelling with amino acids (pulsed-SILAC), to quantify newly expressed proteins in colistin-tolerant subpopulations of Pseudomonas aeruginosa biofilms (colistin is a ‘last-resort' antibiotic against multidrug-resistant Gram-negative patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 55 publications
6
127
0
4
Order By: Relevance
“…We also found that the mutations were not attributed to highly mutagenic growth conditions, as there was no significant increase in mutation rates with ROS treatment (electronic supplementary material, figure S2) compared with control medium, with the mutation rates similar to previous reports [38]. Moreover, the cell populations did not develop mutations in the mutS gene, which is important in mismatch repair and its mutation can lead to the emergence of multiple phenotypic variants [53].…”
Section: Resultssupporting
confidence: 84%
“…We also found that the mutations were not attributed to highly mutagenic growth conditions, as there was no significant increase in mutation rates with ROS treatment (electronic supplementary material, figure S2) compared with control medium, with the mutation rates similar to previous reports [38]. Moreover, the cell populations did not develop mutations in the mutS gene, which is important in mismatch repair and its mutation can lead to the emergence of multiple phenotypic variants [53].…”
Section: Resultssupporting
confidence: 84%
“…Figure S4 shows the structural evolution of the LG21 peptide when it interacts with the Psl. It is observed that the middle residues (6)(7)(8)(9)(10)(11)(12)(13)(14) are the main contributors to the helical conformation. The reason could be that the presence of carbohydrate chain (Psl) in the solution decreases the polar nature of water to form hydrogen bonds with the middle residues and the increasing hydrophobic interactions within the peptide induces the helical structure, whereas the terminal residues still have a random-coil structure by being exposed to the aqueous solution.…”
Section: Molecular Dynamics (Md) Simulation Of Psl-lg21 Binding Modementioning
confidence: 99%
“…On the other hand, when revisited, widely used natural antimicrobial compounds demonstrated a broad efficacy against biofilm-forming microorganisms ([14–17]; Table 1). For example, the established antimicrobial preservative acetic acid is highly effective in the treatment of chronic wounds infected with biofilm-forming P. aeruginosa [18].…”
Section: Treatment Strategies For Biofilm Infectionsmentioning
confidence: 99%
“…Thereby, treatment with the last resort polymyxin antibiotic colistin is more effective compared to many other antibiotics under anaerobic conditions [11]. In vitro treatment of biofilms, though, induces the formation of a subpopulation of colistin-tolerant cells that can subsequently be killed combining colistin with erythromycin, ciprofloxacin or tetracycline [12][13][14]. established antimicrobial preservative acetic acid is highly effective in the treatment of chronic wounds infected with biofilm-forming P. aeruginosa [18].…”
Section: Treatment Strategies For Biofilm Infectionsmentioning
confidence: 99%